Management of Integrity Zone Data Information System in Higher Education - Isworo Indriati; Sudijono Sastroatmodjo; Wahyudin Wahyudin; Udy Wachyudi; Angga Rizky P (Educational Management, 2024)
The purpose of this study is to establish a data information system model for the Integrity Zone in higher education. ZI (Integrity Zone) is a predicate given to agencies/institutions whose administrators and staff are involved in realizing Corruption-Free Area (WBK) and Clean Serving Bureaucratic Area (WBBM) at the central and regional levels. One of the government agencies/institutions that implements the ZI WBK and WBBM programs is UNNES Faculty of Law. The research method using the access system approach and system development is an efficient way to solve the problems that started by identifying a number of requirements to create an efficient and functional application. However, the system development process includes several tasks that can be divided into several steps. With the discovery of System Governance has not been implemented properly. The presence of ZI at UNNES Faculty of Law can be realized through bureaucratic reform, especially in terms of preventing and improving corruption problem and quality of public services. WBK stands for Corruption-Free Area. WBBM stands for Clean Serving Bureaucratic Area. WBBM is a predicate given to work units that fulfils most of the five WBK programs, and a program to strengthen the quality of public services.